Type 1 Arnold Chiari Malformation With Syringomyelia: A Case Report - Akbar, Muhammad; Armalia, Armalia; Tammasse, Jumraini; Goysal, Yudy; Basri, Muhammad I (Journal of Case Reports in Dental Medicine, 2021)
Objective: Arnold Chiari Malformation is a pathological herniation of the hindbrain through the foramen magnum into the cervical canal, characterized by herniation of the inferior cerebellar tonsils of 3-5 mm 30-70% accompanied by syringomyelia.Methods: This case presents a 16-year-old woman who came to the Neurophysiology Section of Â Wahidin Sudirohusodo Hospital with complaints of weakness and numbness in her left arm since last year. It all started with pain in the back of the head and neck after a heavy sneeze three years ago, and since then, the pain has been inconsistent. The patient has gone to the doctor and was given medication, but his symptoms are not improving. Clinical manifestations get worse after the patient uses a computer or mobile phone. Physical examination revealed atrophy of the thenar and hypothenar muscles and sensory dissociation in the left arm's 5th cervical to a first thoracic dermatome. NCV and F-wave examination showed no signs of radiculopathy, plexopathy, or neuropathy. Furthermore, cervical magnetic resonance imaging (MRI) showed Arnold Chiari Malformation Type-1 with syringomyelia extending from cervical spinal cord segment-2 to thoracic-1.Result: This patient was diagnosed based on history, physical examination, nerve conduction study, and MRI spine. There was no clinical improvement after therapy.Conclusion: The clinical picture of Arnold Chiari Malformation Type-1 is so varied that it requires detailed information to diagnose.